Polemik Pengaturan Kepemilikan Data Pribadi: Urgensi Untuk Harmonisasi Dan Reformasi Hukum Di Indonesia - Anggraeni, Setyawati Fitri (Jurnal Hukum & Pembangunan, 2018)
Big data is the large volume of data available in information traffic and is considered to have economic value in the present. The data is collected, stored, and sometimes analyzed for the purpose of providing economic benefits to certain organizations. As individuals who provide the data to an organization, we believe that the data will be protected and kept confidential. However, the reality is sometimes different. Laws and regulations that specifically regulate the collection, storage, publication and protection of personal data very needed. This paper will discuss the legal framework for personal data and their protection in Indonesia. At the same time, this paper will also review the regulations applicable in Singapore and the European Union as a reference for legal reform.